Concentrações de ferro, cobre, zinco e manganês em equinos da raça Puro-sangue Lusitano, antes e após exercício1 - Minini, Rodrigo A.B.; Laposy, Cecília B.; Neto, Hemann B.; Melchert, Alessandra [UNESP]; Giuffrida, Rogério; De Rossi, Hugo; do Valle, Heloisa F.D. (FapUNIFESP (SciELO), 2013)
In order to evaluate the sera concentrations of iron, copper, zinc and manganese trace minerals in thirty Pure-bred Lusitano athlete horses before and after exercise certified by clinical and laboratory assessments were studied. Blood samples were taken before and after 20 minutes of a dairy trot and gallop slight training, perfomed in a sandy floor ring, to measure the mineral concentrations, by atomic absorption spectrophotometry. It was observed that after exercising, the serum activity of iron did not change (P=0.2365), whereas copper values have significantly risen after training (P<0.001). On the other hand, zinc and manganese trace minerals decreased after exercise (P<0.001). In conclusion, it is possible to consider that the short time exercise may trigger sweating and consequently to change the seru.
Serum concentration of iron, copper, zinc and manganese in Pure-bred Lusitano horses, before and after exercise
Keywords: Athletic horses.; Physical activity; Trace minerals